2005
DOI: 10.1038/sj.bjc.6602814
|View full text |Cite
|
Sign up to set email alerts
|

Effects of platinum/taxane based chemotherapy on acute perfusion in human pelvic tumours measured by dynamic MRI

Abstract: Dynamic contrast enhanced MRI (DCE-MRI) is being used increasingly in clinical trials to demonstrate that vascular disruptive and antiangiogenic agents target tumour microcirculation. Significant reductions in DCE-MRI kinetic parameters are seen within 4 -24 and 48 h of treatment with vascular disruptive and antiangiogenic agents, respectively. It is important to know whether cytotoxic agents also cause significant acute reductions in these parameters, for reliable interpretation of results. This study investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…This includes the natural biological variability of parameters such as K trans /ADC, the variability inherent in the measuring instruments (that is, the MRI scanner) and knowledge of additional errors induced by appraisers or analysis techniques. There have been a few published studies documenting measurement error in body applications for DCE-MRI and DW-MRI and most published studies are from institutions with considerable technical expertise [66,100,101]; there are few larger scale multicentre studies [102]. Despite these limitations, it is widely recognized that reductions in K trans of between 30-50% probably represents a significant change for extracranial malignancies where a therapy induced change can be inferred.…”
Section: Reproducibilitymentioning
confidence: 97%
See 1 more Smart Citation
“…This includes the natural biological variability of parameters such as K trans /ADC, the variability inherent in the measuring instruments (that is, the MRI scanner) and knowledge of additional errors induced by appraisers or analysis techniques. There have been a few published studies documenting measurement error in body applications for DCE-MRI and DW-MRI and most published studies are from institutions with considerable technical expertise [66,100,101]; there are few larger scale multicentre studies [102]. Despite these limitations, it is widely recognized that reductions in K trans of between 30-50% probably represents a significant change for extracranial malignancies where a therapy induced change can be inferred.…”
Section: Reproducibilitymentioning
confidence: 97%
“…The initial area under the gadolinium concentration curve (IAUGC) is a relatively robust and simple kinetic parameter to derive and is able to characterize all enhancing regions without the problems associated with model fitting failures. IAUGC has been recommended as a practical substitute for K trans in clinical studies by several authors [63][64][65][66][67]. If IAUGC is to be used then it needs to be validated for this purpose.…”
Section: Technology Quantification and Interpretationmentioning
confidence: 99%
“…These two parameters have been shown to be sensitive to tumor growth and treatment response (e.g., Refs. [3][4][5]. Most models employed in the quantitative analysis of DCE-MRI data require knowledge of the time course of the concentration of the CA in arterial blood, otherwise known as the arterial input function (AIF).…”
mentioning
confidence: 99%
“…More likely, it is the direct cytotoxic effect of the chemotherapy agent(s) on tumor cells which decreases the angiogenic signal required to maintain the tumor neovascularity. However, it has been shown recently [17], that within the limits of test-retest reproducibility, no change in measured tumor K trans , k ep , or v e could be identified 1 day after the first dose of taxane or platinum based conventional cytotoxic regimens. These results suggest that cytotoxic therapies, even if ultimately effective in reducing tumor size, may not manifest in alterations in tumor neovasculature in the early posttreatment setting.…”
Section: Dce-mri Uses In Clinical Studiesmentioning
confidence: 95%
“…Given the large number of image-based inputs required for estimating tumor K trans , the difficulties in standardizing MR imaging intensities, and the variety of imaging and modeling techniques in use, technical variations may overwhelm the ability of researchers to reliably depict subtle alterations in tumor vascularity. Indices of repeatability for DCE-MRI metrics have suggested that with current techniques, post treatment decrements in tumor K trans on the order of 40% are required to be considered a significant indicator of antivascular activity [16][17][18].…”
Section: Vascular Physiologic Parameters: Definition Of Termsmentioning
confidence: 99%